: Análisis de contenido de los influencers de moda en Instagram y como las tendencias influyen en la toma de decisiones en los jóvenes de 18-24 años de la UNACH, periodo julio-diciembre 2022 - Rodas Segarra, Bryan Guillermo (2023)
ABSTRACT: The objective of this project is to analyze the content of fashion influencers on Instagram and how trends influence the decision-making of young people aged 18-24 at UNACH. The methodology has a mixed nature, an inductive-deductive research method was applied, with a documentary design, and a descriptive type. The population chosen for development were students from the different faculties of the National University of Chimborazo. The results show that fashion influencers play a crucial role in this scenario. They have a powerful impact on the choice of who young people follow and, ultimately, on the trends they adopt. One of the most used platforms is Instagram.